Physiological harmfulness of xylophagous insects in poplar and aspen stands in the Left-Bank Forest-Steppe - Skrylnyk , Y. Y.; Zhupinska , K. Y.; Koshelyaeva , Y. V.; Meshkova , V. L. (Forestry and Forest Melioration, 2023)
Introduction Poplars and aspens (Populus sp.) are common in forest stands, shelterbelts, rural landscaping, and in special plantations as short-rotation woody crops; they are promising tree species for biofuel and bioenergy production. Wood-boring insects browse galleries in a stem or branches that interrupt sap circulation and promote infestation by plant pathogens. Some of these insects can additionally weaken trees using foliage, bark, or phloem for maturation feeding. All these effects comprise the physiological harmfulness of wood-boring insects, whereas their technical harmfulness depends on the size and depth of the galleries, their location at the stem, and the timber value of a given tree species. The approach of wood-boring insect harmfulness assessment was suggested by E. Mozolevskaya and it is implemented for oak, pine, spruce, birch, and elm. It was shown that the harmfulness of the same insect species varies significantly depending on environmental conditions and population density. The aim of the research was to evaluate the physiological harmfulness of xylophagous insects for Populus sp. in the Left-Bank Forest-Steppe considering the ability of these insects to colonize and damage trees under certain health, transmit the pathogens, as well as host range and occurrence. Materials and Methods The research was carried out in 2019–2022 in Poltava, Sumy, and Kharkiv regions at the archive plantation of poplar clones, forest stands, and forest shelterbelts. The collections and research of Yu. Skrylnik since 2006 in the specified territories were also included in the analysis. In the analysis, only those insect species were used, for which the development in the stems and branches of Populus sp. was proved by our research and/or supported by publications. The range of host plants and the occurrence of insects were estimated. Their physiological harmfulness was calculated as the sum of scores for their physiological activity (ability to colonize trees under certain health condition), ability to damage the trees during maturation feeding, and ability to vector the pathogens. Results and Conclusions In the study, 72 insect species were analyzed, particularly 40 Cerambycidae, 19 Buprestidae, 7 Curculionidae, 2 Sesiidae, and 3 Cossidae. The proportion of abundant species was the highest among Scolytinae: Xyleborini. Species with a high physiological activity predominate among monophagous insects, particularly, Agrilus suvorovi, Cryptorhynchus lapathi, Xyleborus cryptographus, Paranthrene tabaniformis, Acossus terebra. Only five species (S. populnea, S. octopunctata, S. perforata, S. scalaris, S. carcharias) can cause significant damage to trees during maturation feeding by foliage or bark of branches. The average score of physiological harmfulness is the highest among abundant xylophagous species, it is almost twice as low in common species, and almost two times less in rare and single species. High physiological harmfulness (10 and more) for poplars and aspens is estimated for nineteen xylophagous species, particularly, 13 for S. populnea and S. carcharias, and 12 for Cryptorhynchus lapathi, Trypodendron signatum, Tremex fuscicornis, and Xyleborini species. 3 Tab., 4 Fig., 35 Ref.